A catalyst for preparing acrylonitrile and its preparation method and application

By combining the modified molecular sieve support and pre-loaded metal oxide, the problem of low stability and selectivity of acrylonitrile catalysts in the prior art is solved, and a catalytic effect with high selectivity and high stability under high load is achieved.

CN116060083BActive Publication Date: 2025-01-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111300848.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-04
Publication Date
2025-01-03
Estimated Expiration
2041-11-04

AI Technical Summary

Technical Problem

The existing acrylonitrile catalysts have problems of poor stability and low selectivity under high loads, especially due to poor instability and uniformity of inorganic non-metallic materials, which leads to a decrease in selectivity of the catalyst during long-term operation and an increase in by-products.

Method used

Modified molecular sieve as a support, pre-loaded metal oxides such as Fe, Co, Ni, etc., and prepare catalysts through roasting and slurry cooking steps to ensure the pore structure and uniformity of the catalyst, improve its surface area and strength, and enhance ammonia. Adsorption and storage capabilities of molecules.

Benefits of technology

It significantly improves the long-term stability and selectivity of the catalyst, reduces the generation of by-products, and improves the conversion and selectivity of acrylonitrile.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116060083B_ABST
    Figure CN116060083B_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for preparing acrylonitrile, a preparation method thereof and an application thereof. The catalyst of the invention comprises a modified molecular sieve and an active metal component, wherein the pores of the modified molecular sieve are preloaded with a metal oxide, wherein the metal oxide is a metal oxide of at least one of Fe, Co and Ni. When the catalyst is used for preparing acrylonitrile by ammoxidation of propylene, it still has the advantages of good stability and high selectivity under high load.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysts, in particular to a catalyst for preparing acrylonitrile and a preparation method and application thereof. Background Art

[0002] Acrylonitrile (AN) can be used for synthetic fiber acrylic, and is also the raw material for thermoplastic synthetic resins such as acrylonitrile-butadiene-styrene (ABS), styrene-acrylonitrile (SAN), nitrile rubber, adiponitrile, acrylamide and other derivatives. It is one of the important products of petrochemical industry. At present, the process technology of producing acrylonitrile by propylene ammoxidation has become increasingly mature, among which the high stability and high selectivity catalyst used in fluidized bed reaction is the technical core of the process. The development of acrylonitrile catalyst with excellent performance is a hot topic of concern in the acrylonitrile industry.

[0003] In actual industrial applications, it is found that the selectivity of acrylonitrile catalysts tends to be significantly reduced after long-term operation due to various reasons such as low specific surface area, structural damage, loss of active components, etc., and the by-products of deep oxidation such as carbon monoxide and carbon dioxide are significantly increased. Therefore, improving the long-term stability and selectivity of acrylonitrile catalysts is of great practical significance.

[0004] CN106955717A discloses a method for preparing an efficient and wear-resistant acrylonitrile catalyst, wherein the method adds nano inorganic non-metallic materials such as activated clay or montmorillonite, places the dried particles in a roasting furnace, and roasts and shapes them under the condition of maintaining a constant temperature in stages to obtain an acrylonitrile catalyst. However, since the inorganic non-metallic materials used do not have a stable and uniform structure of their own and are difficult to disperse uniformly in the slurry, the particle size and structural uniformity of the catalyst finally obtained are poor, which is not conducive to long-term stable operation. CN107398285 discloses a method for preparing an acrylonitrile catalyst by ammoxidation of propylene, wherein powders such as montmorillonite and diatomaceous earth, a carrier modifier, are added during the preparation process, which is conducive to improving the problems of poor selectivity and low stability of the catalyst.

[0005] It can be seen that the composite oxide catalyst used for propylene ammoxidation to prepare acrylonitrile in the prior art has problems such as poor stability and low selectivity under high load, which need to be solved urgently. Summary of the invention

[0006] In view of the deficiencies of the prior art, the present invention provides a catalyst for preparing acrylonitrile, a preparation method and application thereof. When the catalyst is used for preparing acrylonitrile by propylene ammoxidation, it still has the advantages of good stability and high selectivity under high load.

[0007] The first aspect of the present invention provides a catalyst for preparing acrylonitrile, which comprises a modified molecular sieve and an active metal component, wherein the pores of the modified molecular sieve are preloaded with a metal oxide, and the metal oxide is a metal oxide of at least one of Fe, Co and Ni.

[0008] Furthermore, based on the weight of the catalyst, the content of the modified molecular sieve is 35% to 65%, and the content of the active metal component is 35% to 65%.

[0009] Furthermore, the active metal component has the following general formula: Mo 10 Bi a X b Y c Z d O x , X is selected from at least one of Li, Na, K, Rb and Cs, Y is selected from at least one of Ca, Mg and Ba; Z is selected from at least one of Fe, Mn, Co, Ni, Cr, W, Zr, Pr, V, Ti, Pt and Nb; a is in the range of 0.02 to 6.0; b is in the range of 0.01 to 2.0, c is in the range of 0.50 to 8.0, and d is in the range of 0.50 to 10.0; x is the number of oxygen atoms required to satisfy the valence of other elements.

[0010] Furthermore, based on the weight of the modified molecular sieve, the content of the metal oxide in the pores is 0.5% to 2.0%.

[0011] Furthermore, the metal oxide preloaded in the pores preferably contains at least Co and Ni at the same time, and more preferably the molar ratio of Co to Ni is 1:0.8 to 1:1.2.

[0012] Furthermore, the modified molecular sieve is obtained by modifying at least one molecular sieve selected from SBA-15, KIT-6 or ZSM-5 by pre-loading metal oxides in the pores.

[0013] Furthermore, the average particle size of the SBA-15, KIT-6 or ZSM-5 molecular sieve is 60 to 120 meshes; the specific surface area is 100 to 600 m 2 / g.

[0014] Furthermore, the acid site content of the catalyst measured by ammonia temperature-programmed desorption (NH3-TPD) is 0.25 to 0.50 mmol / g.

[0015] A second aspect of the present invention provides a method for preparing a catalyst for preparing acrylonitrile, comprising the following steps:

[0016] (a) fully mixing a metal precursor solution of at least one of Fe, Co and Ni with a molecular sieve, and calcining the dried slurry to obtain a modified molecular sieve;

[0017] (b) preparing a solution I containing the Mo component and a solution II containing the Bi, X, Y, and Z components respectively;

[0018] (c) adding the modified molecular sieve obtained in step (a) to the solution I obtained in step (b), mixing them evenly, and then mixing them with the solution II, and continuing to boil the slurry to obtain a mixed slurry;

[0019] (d) drying and calcining the mixed slurry obtained in step (c) to obtain a catalyst for preparing acrylonitrile.

[0020] Furthermore, in step (a), the metal precursor is preferably one or more of water-soluble inorganic acid salts and / or water-soluble organic acid salts, and is further preferably one or more of halides, alkoxides, nitrates or acetates.

[0021] Furthermore, in step (a), the metal precursor solution is fully mixed with the molecular sieve, preferably the molecular sieve is first mixed with water, and then the metal precursor solution is slowly added under stirring. The stirring temperature is 25 to 60°C, preferably 30 to 50°C, the stirring time is 1 to 5 hours, preferably 2 to 3 hours; the stirring speed is preferably 200 to 800 rpm,

[0022] Furthermore, in step (a), the drying conditions are: drying temperature is 50-100° C., and drying time is 6-12 hours, preferably 8-10 hours. Drying is performed in an air atmosphere.

[0023] Furthermore, in step (a), the calcination conditions are as follows: the calcination temperature is 480-650° C., preferably 550-600° C., the calcination time is 1-5 hours, preferably 2-3 hours, and the calcination is carried out in an air atmosphere.

[0024] Furthermore, in step (b), the Mo-containing element precursor is preferably one or more of a water-soluble inorganic acid salt, a water-soluble organic acid salt or an oxygen-containing acid ammonium salt of Mo, more preferably an oxygen-containing acid ammonium salt of Mo, such as (NH4)6Mo7O 24 The element precursor containing Bi, X, Y, and Z is preferably a water-soluble inorganic acid salt or a water-soluble organic acid salt, and is further preferably one or more of a halide, an alkoxide, a nitrate, or an acetate.

[0025] Furthermore, in step (b), the mixing is carried out under conventional mixing conditions until the mixture is uniformly mixed.

[0026] Furthermore, in step (c), the conditions for cooking the slurry are: a temperature of 100 to 180° C., preferably 120 to 150° C., a time of 5 to 60 min, and a stirring speed of 200 to 800 rpm, preferably 400 to 500 rpm.

[0027] Furthermore, in step (d), the drying is spray drying, and the drying conditions are: the heat source is air, the drying temperature is 200-480°C, preferably 300-400°C, the drying time is 0.5-4h, preferably 0.5-1.5h, and the average diameter of the spray droplets is 40-200μm, preferably 40-180μm.

[0028] Furthermore, in step (d), the calcination conditions are: carried out in an oxygen-containing atmosphere, the calcination temperature is 200-700° C., preferably 400-650° C., and the calcination time is 3-8 hours, preferably 4-6 hours.

[0029] The third aspect of the present invention provides use of the above catalyst or the catalyst prepared by the above method in the preparation of acrylonitrile.

[0030] The application is specifically as follows: in the presence of the catalyst, propylene undergoes an ammoxidation reaction in the presence of ammonia and oxygen to generate acrylonitrile.

[0031] The specific reaction conditions include: the molar ratio of propylene / ammonia / air (based on the oxygen contained) is 1:1.2-1.3:9.6-10.0, the reaction temperature is 420-435°C, the reaction pressure is 0.06-0.14 MPa, and the weight hourly space velocity is 0.06-0.10 h -1 .

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] The catalyst of the present invention uses a solid molecular sieve as a carrier, which not only provides a good specific surface area for the catalyst, but also has a high strength, and can reduce the wear of the catalyst after long-term operation.

[0034] In the catalyst of the present invention, a small amount of transition metal with catalytic activity is loaded in the pores of the solid carrier in advance by the method of impregnation and roasting. The coordination of the transition metal ions in the pores with the raw material ammonia molecules and the synergistic effect of the B acid characteristics of the molecular sieve carrier enable the catalyst to maintain a certain acidity, which can improve the adsorption and storage of ammonia molecules by the catalyst, thereby improving the selectivity of acrylonitrile and greatly reducing the content of two carbons in the by-product. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a high-resolution transmission electron micrograph of the modified molecular sieve prepared in Example 1. DETAILED DESCRIPTION

[0036] The method for measuring the specific surface area and pore size in the present invention adopts a Tristar physical adsorption instrument for measurement. Before the sample is tested, it is necessary to perform a heating vacuum degassing treatment. The porosity of the sample is measured at 77K, and the specific surface area is calculated by the Brunauer-Emmett-Teller (BET) method. The distribution of pore size and pore volume can be calculated from the isothermal adsorption branch using the Barrettner-Joyner-Halenda (BJH) model.

[0037] The present invention uses the AutoChemII2920 fully automatic physical and chemical adsorption instrument produced by Micromeritics to measure the acid site content of the catalyst. The sample is first pretreated in a helium atmosphere at 150°C for 4 hours, then the catalyst is placed in a 10% NH3-He atmosphere, and finally the ammonia desorption curve is detected in a He atmosphere heated to 800°C at a rate of 10°C / min.

[0038] The modified molecular sieve morphology of the present invention was characterized by a high-angle annular dark field scanning transmission electron microscope (HAADF-STEM, model FEI Talos F200X). The catalyst element component analysis was performed by energy dispersive X-ray (EDX), and the microstructure and chemical composition were analyzed and observed under 200 kV conditions.

[0039] In the present invention, gas chromatography is used to perform online analysis on the product gas, and the conversion rate of propylene, the selectivity of acrylonitrile and the single-pass yield are used as indicators for evaluating the performance of the catalyst, and the definitions of the two are as follows:

[0040] Acrylonitrile conversion (%) = (moles of propylene reacted / moles of propylene fed) × 100%

[0041] Acrylonitrile selectivity (%) = (moles of acrylonitrile produced / moles of propylene reacted) × 100%

[0042] Acrylonitrile single-pass yield (%) = (acrylonitrile produced moles / propylene feed moles) × 100%

[0043] [Example 1]

[0044] Weigh 85.0 g of ZSM-5 molecular sieve (100 mesh, specific surface area 350 m 2 / g) was dispersed in 200mL of water, and 20mL of 0.29mol / L Co(NO3)2·6H2O and 20mL of 0.29mol / L Ni(NO3)2·6H2O aqueous solution were slowly added at 250rpm. After the addition was completed, stirring was continued at 25°C for 2h, and the solution was placed in an oven at 80°C for 10h until it was completely dried. Finally, the obtained solid was ground into fine particles and calcined in a muffle furnace at 600°C for 4h with air to obtain a modified molecular sieve Z-Co / Ni-1.0wt% (indicates that the pores are pre-loaded with a total mass fraction of 1.0% CoO and NiO in the ZSM-5 molecular sieve). The high-resolution transmission electron microscopy characterization results of the modified molecular sieve after pre-loading the metal are shown in Figure 2. Figure 1 As shown, it was observed that small particles of metal oxide were loaded in the pores of the modified molecular sieve.

[0045] 93.7 g (NH4)6Mo7O 24 ·4H2O is heated and dissolved in water to obtain solution I; 9.6 grams of Bi(NO3)3·5H2O, 62.1 grams of Ni(NO3)2·6H2O, 30.2 grams of Fe(NO3)3·9H2O, 20.3 grams of Mg(NO3)2·6H2O and 0.86 grams of CsNO3 are dissolved in water to obtain solution II. The preloaded molecular sieve carrier Z-Co-2wt% is added to solution I, and after stirring and evenly dispersing, solution II is added thereto, and stirred at 100°C and 300rpm for 0.5 hours to obtain slurry. The slurry is spray dried at a drying temperature of 350°C and a drying time of 0.5 hours to obtain particles, which are calcined at 600°C in an air atmosphere for 3 hours to obtain acrylonitrile catalyst A.

[0046] The reaction conditions for the above catalyst to produce acrylonitrile by propylene ammoxidation are: On a millimeter fluidized bed reactor, reaction temperature: 420°C; reaction pressure: 0.085Mpa; catalyst loading: 300g; catalyst propylene load (WWH): 0.06h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.7. The conversion rate, selectivity and other data of the operation are detailed in the table below.

[0047] [Example 2]

[0048] Weigh 85.0 g of KIT-6 molecular sieve (120 mesh, specific surface area 300 m 2 / g) was dispersed in 200mL of water, and 20mL of 0.27mol / L Fe(NO3)3·9H2O and 20mL of 0.29mol / L Ni(NO3)2·6H2O aqueous solution were slowly added at 250rpm. After the addition was completed, stirring was continued at 25°C for 2h, and the solution was placed in an oven at 80°C for 10h until it was completely dried. Finally, the obtained solid was ground into fine particles and calcined in a muffle furnace at 600°C with air for 4h to obtain a pre-loaded molecular sieve carrier K-Fe / Ni-1.0wt% (indicating that the pores were pre-loaded with a total mass fraction of 1.0% Fe2O3 and NiO of KIT-6 molecular sieve).

[0049] 93.7 g (NH4)6Mo7O 24 ·4H2O is heated and dissolved in water to obtain solution I; 9.6 grams of Bi(NO3)3·5H2O, 62.1 grams of Ni(NO3)2·6H2O, 30.2 grams of Fe(NO3)3·9H2O, 20.3 grams of Mg(NO3)2·6H2O and 0.86 grams of CsNO3 are dissolved in water to obtain solution II. The preloaded molecular sieve carrier K-Fe-3wt% is added to solution I, and after stirring and evenly dispersing, solution II is added thereto, and stirred at 100°C and 300rpm for 0.5 hours to obtain slurry. The slurry is spray-dried at a drying temperature of 350°C and a drying time of 0.5 hours to obtain particles, which are calcined at 600°C in an air atmosphere for 3 hours to obtain acrylonitrile catalyst B.

[0050] The reaction conditions for producing acrylonitrile by ammoxidation of propylene are the same as those in Example 1. The conversion rate, selectivity and other data of the operation are shown in the table below.

[0051] [Example 3]

[0052] Weigh 85.0 g of SBA-15 molecular sieve (120 mesh, specific surface area 420 m 2 / g) was dispersed in 200mL of water, and 40mL of 0.29mol / L Co(NO3)2·6H2O and 20mL of 0.27mol / L Fe(NO3)3·9H2O aqueous solution were slowly added at 250rpm. After the addition was completed, stirring was continued at 25°C for 2h, and the solution was placed in an oven at 80°C for 10h until it was completely dried. Finally, the obtained solid was ground into fine particles and calcined in a muffle furnace at 600°C with air for 4h to obtain a pre-loaded molecular sieve carrier S-Co / Ni-1.5wt% (indicating that the pores were pre-loaded with SBA-15 molecular sieves with a total mass fraction of 1.5% CoO and Fe2O3).

[0053] 93.7 g (NH4)6Mo7O 24·4H2O was heated and dissolved in water to obtain solution I; 9.6 g Bi(NO3)3·5H2O, 62.1 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, 20.3 g Mg(NO3)2·6H2O and 0.86 g CsNO3 were dissolved in water to obtain solution II. The preloaded molecular sieve carrier Z-Co-2wt% was added to solution I, and after stirring and evenly dispersing, solution II was added thereto, and stirred at 100°C and 300 rpm for 0.5 hours to obtain slurry. The slurry was spray dried at a drying temperature of 350°C and a drying time of 0.5 hours to obtain particles, which were calcined at 600°C in an air atmosphere for 3 hours to obtain acrylonitrile catalyst C.

[0054] The reaction conditions for producing acrylonitrile by ammoxidation of propylene are the same as those in Example 1. The conversion rate, selectivity and other data of the operation are shown in the table below.

[0055] [Example 4]

[0056] Weigh 85.0 g of ZSM-5 molecular sieve (100 mesh, specific surface area 350 m 2 / g) was dispersed in 200mL of water, and 40mL of 0.29mol / L Co(NO3)2·6H2O aqueous solution was slowly added at 250rpm. After the addition was completed, stirring was continued at 25°C for 2h. The solution was placed in an oven at 80°C for 10h until completely dried. Finally, the obtained solid was ground into fine particles and calcined in a muffle furnace at 600°C with air for 4h to obtain a pre-loaded molecular sieve carrier Z-Co-1.0wt% (indicating that the pores were pre-loaded with a total mass fraction of 1.0% CoO of ZSM-5 molecular sieve).

[0057] 93.7 g (NH4)6Mo7O 24 ·4H2O was heated and dissolved in water to obtain solution I; 9.6 g Bi(NO3)3·5H2O, 62.1 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, 20.3 g Mg(NO3)2·6H2O and 0.86 g CsNO3 were dissolved in water to obtain solution II. The preloaded molecular sieve carrier Z-Co-2wt% was added to solution I, and after stirring and evenly dispersing, solution II was added thereto, and stirred at 100°C and 300 rpm for 0.5 hours to obtain slurry. The slurry was spray dried at a drying temperature of 350°C and a drying time of 0.5 hours to obtain particles, which were calcined at 600°C in an air atmosphere for 3 hours to obtain acrylonitrile catalyst D.

[0058] The reaction conditions for producing acrylonitrile by ammoxidation of propylene are the same as those in Example 1. The conversion rate, selectivity and other data of the operation are shown in the table below.

[0059] [Example 5]

[0060] Weigh 85.0 g of SBA-15 molecular sieve (100 mesh, specific surface area 420 m 2 / g) was dispersed in 200mL of water, and 60mL of 0.29mol / L Co(NO3)2·6H2O aqueous solution was slowly added at 250rpm. After the addition was completed, stirring was continued at 25°C for 2h. The solution was placed in an oven at 80°C for 10h until completely dried. Finally, the obtained solid was ground into fine particles and calcined in a muffle furnace at 600°C with air for 4h to obtain a pre-loaded molecular sieve carrier S-Co-1.5wt% (indicating that the pores were pre-loaded with SBA-15 molecular sieves with a total mass fraction of 1.5% CoO).

[0061] 93.7 g (NH4)6Mo7O 24 ·4H2O was heated and dissolved in water to obtain solution I; 9.6 g Bi(NO3)3·5H2O, 62.1 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, 20.3 g Mg(NO3)2·6H2O and 0.86 g CsNO3 were dissolved in water to obtain solution II. The preloaded molecular sieve carrier Z-Co-2wt% was added to solution I, and after stirring and evenly dispersing, solution II was added thereto, and stirred at 100°C and 300 rpm for 0.5 hours to obtain slurry. The slurry was spray dried at a drying temperature of 350°C and a drying time of 0.5 hours to obtain particles, which were calcined at 600°C in an air atmosphere for 3 hours to obtain acrylonitrile catalyst E.

[0062] The reaction conditions for producing acrylonitrile by ammoxidation of propylene are the same as those in Example 1. The conversion rate, selectivity and other data of the operation are shown in the table below.

[0063] [Example 6]

[0064] Weigh 85.0 g of ZSM-5 molecular sieve (100 mesh, specific surface area 350 m 2 / g) was dispersed in 200mL of water, and 40mL of 0.29mol / L Ni(NO3)2·6H2O and 40mL of 0.29mol / L Co(NO3)2·6H2O aqueous solution were slowly added at 250rpm. After the addition was completed, stirring was continued at 25°C for 2h, and the solution was placed in an oven at 80°C for 10h until it was completely dried. Finally, the obtained solid was ground into fine particles and calcined in a muffle furnace at 600°C with air for 4h to obtain a pre-loaded molecular sieve carrier Z-Co / Ni-2.0wt% (indicating that the pores were pre-loaded with a ZSM-5 molecular sieve with a total mass fraction of 2.0% CoO and NiO).

[0065] 93.7 g (NH4)6Mo7O 24 ·4H2O was heated and dissolved in water to obtain solution I; 9.6 g Bi(NO3)3·5H2O, 62.1 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, 20.3 g Mg(NO3)2·6H2O and 0.86 g CsNO3 were dissolved in water to obtain solution II. The preloaded molecular sieve carrier Z-Co-2wt% was added to solution I, and after stirring and evenly dispersing, solution II was added thereto, and stirred at 100°C and 300 rpm for 0.5 hours to obtain slurry. The slurry was spray dried at a drying temperature of 350°C and a drying time of 0.5 hours to obtain particles, which were calcined at 600°C in an air atmosphere for 3 hours to obtain acrylonitrile catalyst F.

[0066] The reaction conditions for producing acrylonitrile by ammoxidation of propylene are the same as those in Example 1. The conversion rate, selectivity and other data of the operation are shown in the table below.

[0067] [Comparative Example 1]

[0068] 93.7 g (NH4)6Mo7O 24 ·4H2O was heated and dissolved in water to obtain solution I; 9.6 g Bi(NO3)3·5H2O, 62.1 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, 20.3 g Mg(NO3)2·6H2O and 0.86 g CsNO3 were dissolved in water to obtain solution II. 85.0 g ZSM-5 molecular sieve (100 mesh, specific surface area 350 m 2 / g) was added to solution I, and solution II was added thereto after being stirred and uniformly dispersed, and stirred at 100°C and 300 rpm for 0.5 hour to obtain slurry. The slurry was spray-dried at a drying temperature of 350°C and a drying time of 0.5 hour to obtain particles, which were calcined at 600°C in an air atmosphere for 3 hours to obtain acrylonitrile catalyst G.

[0069] The reaction conditions for producing acrylonitrile by ammoxidation of propylene are the same as those in Example 1. The conversion rate, selectivity and other data of the operation are shown in the table below.

[0070] [Comparative Example 2]

[0071] Weigh 283 grams of 30% silica sol, slowly add 40 mL of 0.29 mol / L Co(NO3)3·6H2O aqueous solution at 250 rpm, stir continuously for 2 h at 25°C after the addition is completed, place the solution in an oven at 80°C for 10 h until it is completely dried, and finally grind the obtained solid into fine particles and calcine in a muffle furnace at 600°C with air for 4 h to obtain a pre-loaded carrier Si-Co-1.0wt% (indicating that silica is pre-loaded with 1.0% CoO by mass).

[0072] 93.7 g (NH4)6Mo7O 24 ·4H2O was heated and dissolved in water to obtain solution I; 9.6 g Bi(NO3)3·5H2O, 62.1 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, 20.3 g Mg(NO3)2·6H2O and 0.86 g CsNO3 were dissolved in water to obtain solution II. The preloaded molecular sieve carrier Si-Co-1.0wt% was added to solution I, and after stirring and evenly dispersing, solution II was added thereto, and stirred at 100°C and 300 rpm for 0.5 hours to obtain slurry. The slurry was spray dried at a drying temperature of 350°C and a drying time of 0.5 hours to obtain particles, which were calcined at 600°C in air for 3 hours to obtain acrylonitrile catalyst H.

[0073] The reaction conditions for producing acrylonitrile by ammoxidation of propylene are the same as those in Example 1. The conversion rate, selectivity and other data of the operation are shown in the table below.

[0074] [Comparative Example 3]

[0075] Weigh 85.0 g of ZSM-5 molecular sieve (100 mesh, specific surface area 350 m 2 / g) was dispersed in 200mL of water, and 100mL of 0.29mol / L Co(NO3)3·6H2O and 100mL of 0.29mol / L Ni(NO3)3·6H2O aqueous solutions were slowly added dropwise at 250rpm. After the addition was completed, stirring was continued at 25°C for 2h. The solution was placed in an oven at 80°C for 10h until completely dried. Finally, the obtained solid was ground into fine particles and calcined in a muffle furnace at 600°C with air for 4h to obtain a pre-loaded molecular sieve carrier Z-Co / Ni-5.0wt% (indicating that the pores were pre-loaded with a ZSM-5 molecular sieve with a total mass fraction of 5.0% of CoO and NiO).

[0076] 93.7 g (NH4)6Mo7O 24·4H2O is heated and dissolved in water to obtain solution I; 9.6 grams of Bi(NO3)3·5H2O, 62.1 grams of Ni(NO3)2·6H2O, 30.2 grams of Fe(NO3)3·9H2O, and 20.3 grams of Mg(NO3)2·6H2O are dissolved in water to obtain solution II. The pre-loaded molecular sieve carrier Z-Co-10wt% is added to solution I, and after stirring and evenly dispersing, solution II is added thereto, and stirred at 100°C and 300rpm for 0.5 hours to obtain slurry. The slurry is spray-dried at a drying temperature of 350°C and a drying time of 0.5 hours to obtain particles, which are calcined at 600°C in an air atmosphere for 3 hours to obtain acrylonitrile catalyst I.

[0077] The reaction conditions for producing acrylonitrile by ammoxidation of propylene are the same as those in Example 1. The conversion rate, selectivity and other data of the operation are shown in the table below.

[0078] Table 1 Catalyst formulations and characterizations in Examples and Comparative Examples

[0079]

[0080]

[0081] Table 2 Reactor operation data of catalysts in Examples and Comparative Examples

[0082]

Claims

1. A catalyst for preparing acrylonitrile, characterized in that: The catalyst comprises a modified molecular sieve and an active metal component, wherein the pores of the modified molecular sieve are preloaded with a metal oxide, and the metal oxide is at least one metal oxide of Fe, Co, and Ni; The active metal component is generally formulated as follows: Mo 12 Bi a X b Y c Z d O x , X is selected from at least one of Li, Na, K, Rb and Cs, Y is selected from at least one of Ca, Mg and Ba; Z is selected from at least one of Fe, Mn, Co, Ni, Cr, W, Zr, Pr, V, Ti, Pt and Nb; a is in the range of 0.02 to 6.0; b is in the range of 0.01 to 2.0; c is in the range of 0.50 to 8.0; and d is in the range of 0.50 to 10.0; x The number of oxygen atoms necessary to satisfy the valence of each other element; Based on the weight of the modified molecular sieve, the content of metal oxide in the pores is 0.5% to 2.0%; The molecular sieve used in the modified molecular sieve is at least one of SBA-15, KIT-6 or ZSM-5.

2. The catalyst according to claim 1, characterized in that: Based on the weight of the catalyst, the content of the modified molecular sieve is 35% to 65%, and the content of the active metal component is 35% to 65%.

3. The catalyst according to claim 1, characterized in that: The metal oxide preloaded in the pores contains at least Co and Ni.

4. The catalyst according to claim 3, characterized in that: The molar ratio of Co to Ni is 1:0.8~1:1.

2.

5. The catalyst according to claim 1, characterized in that: The acidic site content of the catalyst measured by ammonia temperature programmed desorption (NH3-TPD) is 0.25-0.50 mmol / g.

6. A method for preparing a catalyst according to any one of claims 1 to 5, characterized in that: The following steps are involved: (a) fully mixing a metal precursor solution of at least one of Fe, Co and Ni with a molecular sieve, and calcining the dried slurry to obtain a modified molecular sieve; (b) preparing a solution I containing the Mo component and a solution II containing the Bi, X, Y, and Z components respectively; (c) adding the modified molecular sieve obtained in step (a) to the solution I obtained in step (b), mixing them evenly, and then mixing them with the solution II, and continuing to boil the slurry to obtain a mixed slurry; (d) drying and calcining the mixed slurry obtained in step (c) to obtain a catalyst for preparing acrylonitrile.

7. The preparation method according to claim 6, characterized in that: In step (a), the metal precursor is one or more of water-soluble inorganic acid salts and / or water-soluble organic acid salts.

8. The preparation method according to claim 7, characterized in that: In step (a), the metal precursor is one or more of a halide, a nitrate or an acetate.

9. The preparation method according to claim 6, characterized in that: In step (a), the drying conditions are: drying temperature is 50-100° C., and drying time is 6-12 hours; the roasting conditions are: roasting temperature is 480-650° C., and roasting time is 1-5 hours.

10. The preparation method according to claim 9, characterized in that: In step (a), the drying time is 8-10 hours; the calcination conditions are: the calcination temperature is 550-600° C., and the calcination time is 2-3 hours.

11. The preparation method according to claim 6, characterized in that: In step (c), the conditions for cooking the slurry are: temperature of 100-180° C., time of 5-60 min, and stirring speed of 200-800 rpm.

12. The preparation method according to claim 11, characterized in that: In step (c), the conditions for cooking the slurry are: a temperature of 120-150° C. and a stirring speed of 400-500 rpm.

13. The preparation method according to claim 6, characterized in that: In step (d), the calcination conditions are: carried out in an oxygen-containing atmosphere, the calcination temperature is 200-700° C., and the calcination time is 3-8 hours.

14. The preparation method according to claim 13, characterized in that: In step (d), the calcination conditions are: calcination temperature is 400-650° C., and calcination time is 4-6 hours.

15. Use of the catalyst according to any one of claims 1 to 5 or the catalyst prepared by the method according to any one of claims 6 to 14 in the preparation of acrylonitrile.